Simulated Real-Time Offshore Platform Response Measuring System - Mashuri, Alia (IRC, 2015)
Offshore platform structure undergoes deformation over certain period of time. The deformation occurs due to several loadings including the underwater current, ocean waves, wind forces and mechanical vibration that are produced by the offshore structure itself. Shallow gas phenomena and seabed settlement will also give impact to the surrounding and the structure itself. These environmental factors and loadings acting on the platform tend to affect the integral behaviour and serviceability of the structure and its components. A system is to be developed and tested to measure the response of such structures to the above loading factors. Due to certain constraints, the response measuring system which is based on RTK GPS will be tested in simulated offshore platform deformation scenario. The simulated offshore platform deformation was created by placing an offshore platform scale model on a shaking table, which will be run on certain 3D movement simulating various loading on the offshore platform or other structures. The system was tested on few occasions, and the data collected was analysed, to produce numerical and graphical result. The performance assessment of the RTK GPS-response measuring system will be made and discussed.